Distributional Product of (formula) - Aguirre, Manuel; García, Marta (Nexo Revista Científica, 2012)
Keywords: Distributions, Product of distributions, Dirac`s delta. DOI: http://dx.doi.org/10.5377/nexo.v24i2.661